Robert A. Gahl (Ed.), Etica e politica nella societá del duemila (Roma: Armando Editore, 1998). 176 páginas. ISBN 88-7144-803-0 - Crespo, Ricardo F. (2001)
Fil: Crespo, Ricardo F. Investigador Independiente; Argentina